Systematic Literature Review: Model/ Metode Untuk Meningkatkan Kualitas Perkuliahan Analisis Real - Suci Miranti Hakiki; Rusi Ulfa Hasanah; Siti Hotma Sari Pulungan; Nur Elisah Nasution (Jurnal Mahasiswa Kreatif, 2024)
The Learning Model is a guide for teachers and students in implementing the teaching and learning process. In the model or learning method used, it must aim to improve the learning process or lecture. Therefore, this research will discuss what methods or models can be used to improve the quality of real analysis learning. The method used in this research is Systematic Literature Review (SLR).